Thiophenes - Gronowitz, Salo (Best synthetic methods., 2004)
There is a vast and often bewildering array of synthetic methods and reagents available to organic chemists today. The Best Synthetic Methods series allows any scientist who is interested in the chemical transformations of molecules to choose between all the alternatives and assess their real advantages and limitations. With the emphasis on laboratory use, these volumes represent a comprehensive and practical guide to modern synthetic organic chemistry. This book is the product of the authors many years practical experience and reading of the original literature. It contains a valuable distillation and critical evaluation of the Best Synthetic Methods for the formation and reaction of thiophenes (five membered heterocycles containing a ring sulfur) or polymers containing a thiophene functionality (thienyls). A brief review of each area is provided, but the emphasis in all cases is on describing efficient practical methods to effect the transformations described. The reader can therefore use this book to rapidly review and select the best methods of performing a synthetic conversion to create or modify a specifically substituted thiophene. Although this book contains many references to the original literature, the large number of experimental recipes enables the user to prepare a thiophene derivative without access to the original literature. These features make the handbook especially useful for physicists working in material sciences and organic/pharmaceutical chemists, who rapidly want to find out the availability of (or how to make) a specific thiophene. Contains a systematic description and critical evaluation of the best methods for preparation of thiophenes and polymers containing thiophenes. Rapid location of methods achieved by systematic division of substituents following the periodic table. All chapters are richly illustrated by detailed experimental proceedures for the synthesis of five membered heterocycles containing sulfur.